PENGEMBANGAN KUALITAS PROFESIONAL PENDIDIK DI INDONESIA - . Sopiah (IAIN Pekalongan, 2010)
The delivery of certificate of educators through the processof â€œcertificationâ€ for teachers and lecturers is the logical implicationsof the enactment of Law No. 20 of 2003 on National EducationSystem Law No. 14 of 2005 on Teachers and Lecturers. Teachersand lecturers who have been â€œcertifiedâ€ are ideally already qualifiedby default. It should be after the certification process teachers andlecturers have the awareness and willingness for the quality andenhance the quality and competence themselves. Teachers andlecturers as educators are recognized formally have been â€œworthâ€through that certification process, where the implication is oncertification benefits. Unfortunately once they get the benefits ofcertification of educators and have improved the level of welfare,the improvement of education quality is not necessarily be realized.Therefore it is necessary to find a wise solution, so that certificationis not merely administrative, but more touching the heart of educators,imprints and implications for the increasing competence of educators,so that educators in Indonesia become qualified and profesionaleducators.